Evaluation of polymerization shrinkage stress and cuspal strain in natural and typodont teeth - Luiza Santos CARDOSO; Amanda Alves de OLIVEIRA; Gabrielly D'Paula Muniz BARBOSA; Maria Luisa Prazeres RIBEIRO; Tainah Costa FIRMIANO; Crisnicaw VERÍSSIMO (Sociedade Brasileira de Pesquisa Odontológica, 2024)
Abstract To evaluate the polymerization shrinkage stress and cuspal strain (CS) generated in an artificial (typodont) and in a natural tooth using different resin composites. Twenty artificial and 20 extracted natural molars were selected. Each tooth was prepared with a 4x4 mm MOD cavity. The natural and typodont teeth were divided into four experimental groups (n=10), according to the resin composite used: Filtek Z100 (3M Oral Care) and Beautifil II LS (Shofu Dental). The cavities were filled using two horizontal increments and the CS (µS) was measured by the strain gauge method. Samples were sectioned into stick-shaped specimens and the bond strength (BS) (MPa) was evaluated using a microtensile BS test. Shrinkage stress and CS were analyzed using 3D finite element analysis. No difference was found between the type of teeth for the CS as shown by the pooled averages: Natural tooth: 541.2 A; Typodont model: 591.4 A. Filtek Z100 CS values were higher than those obtained for Beautifil II LS, regardless of the type of teeth. No statistical difference was found for the BS data. Adhesive failures were more prevalent (79.9%). High shrinkage stress values were observed for Filtek Z100 resin, regardless of tooth type. The CS of typodont teeth showed a shrinkage stress effect, generated during restoration, equivalent to that of natural teeth.